Germany profits from growth in Brazil, Russia, India, China, and South Africa: But for how much longer? - Georg Erber; Mechthild Schrooten (DIW Economic Bulletin, 2012)
Brazil, Russia, India, China, and South Africa-the BRICS-show high overall economic growth rates by international standards. Even during the recent economic crisis, most BRICS countries still recorded above-average growth. This development has benefited German foreign trade in particular. This applies especially to automotive and mechanical engineering. However, this geographical reorientation of German export trade in favor of the BRICS countries could soon reach its limits. The institutional and infrastructural conditions of the BRICS are increasingly proving to be bottlenecks for their economic catch-up processes. With the exception of Russia, rapid economic growth in these countries already slowed down in 2011. Further development will depend on the extent to which the governments of the BRICS countries are able to remove the obstacles to growth that have been identified.
Keywords: F14; F15; F43; 330; BRICS; Germany; economic integration; development